Unraveling the risk of dredging on river bars for mineral sand mining: an engineering geological approach - Md. Shohel Rana; A.T.M. Shakhawat Hossain; Md. Fuad Hasan; Md. Aminur Rahman; Pradip Kumar Biswas; Mohammad Nazim Zaman (Discover Geoscience)
Abstract Sand mining using dredging technology from channel bars is a common technique worldwide. To minimize adverse effects of dredging, geo-engineering nature of the soil should be evaluated before mining. Therefore, the present study deals with the potential risks associated with dredging for mineral sand extraction by analyzing the engineering geological properties of the soil from the Brahmaputra River bar and the surrounding areas, Bangladesh. A detailed engineering geological analysis was conducted using field and laboratory testing methods, including Standard Penetration Tests (SPT), mineralogy, grain size distribution (GSD), California Bearing Ratio (CBR), and direct shear tests. The findings divulge that the soil in the study area is light gray, unconsolidated, moderately sorted, poorly graded, and classified as fine-to-medium silty sand. SPT-based liquefaction potential assessments suggest that the soils are highly susceptible to liquefaction, particularly during dredging or seismic events. The study also identifies the risk of localized slumping and soil instability, which exacerbated by micaceous and quartz-rich sands. The CBR results further classify the subgrade as weak to medium-strong, indicating risks of slumping, erosion, and instability. The non-cohesive granular soil in the area may liquefy or be susceptible to erosion, wave attack, bank slope failures, and seepage development during and after dredging as indicated from GSD and direct shear test results. Thus, proper safety precautions, including soil stabilization techniques, controlled dredging, and slope reinforcement, should be taken before dredging on such river bar to minimize risk. This research offers practical guidance for dredging companies to minimize risks and improve soil stability, contributing to safer and more sustainable river bar dredging operations worldwide.